Onset Timing of Hyoid Muscles Activation during Cervical Flexion Is Position-Dependent: An EMG Study - Hirofumi Sageshima; Dagmar Pavlů; Dominika Dvořáčková; David Pánek (Life, 2022)
Due to the high prevalence of neck pain, considerable attention is paid to the function of cervical flexor muscles. Although the deep and superficial cervical flexor muscles have been evaluated, the impact of hyoid muscles on cervical flexion is still not well known. We, therefore, aimed to investigate the activation of hyoid muscles during physiological cervical flexion, and to determine the impact of different starting positions on cervical flexion muscle activation. The activities of bilateral sternocleidomastoid, scalene, suprahyoid, and infrahyoid muscles were evaluated by surface electromyography (EMG) in twenty young healthy volunteers. They performed a repetitive cervical flexion-extension movement, from neutral position of the head to the maximum flexion with the same speed set at eight seconds in a cycle, in three various positions (sitting, standing, and supine). In sitting and standing positions, the group of suprahyoid muscles was activated in advance of other cervical flexor muscles despite only significant differences were found in scalene muscles, and the activation of the group of infrahyoid muscles was time-synchronous with sternocleidomastoid muscles. On the other hand, in supine position, the activation of all measured cervical flexor muscles was significantly earlier and longer than in the other two positions. This study confirmed the empirical suggestion that hyoid muscles contributed to cervical flexion, and it confirmed that muscle activation was position dependent, even if the given movement is nearly identical.